Comparative activity of dimethyl fumarate derivative IDMF in three models relevant to multiple sclerosis and psoriasis - Yulin He; Guiyi Gong; Geovani Quijas; Simon Ming‐Yuen Lee; Ratan K. Chaudhuri; Krzysztof Bojanowski (FEBS Open Bio)
Dimethyl fumarate (DMF) is an anti‐inflammatory and immunoregulatory medication used to treat multiple sclerosis (MS) and psoriasis. Its skin sensitization property precludes its topical use, which is unfortunate for the treatment of psoriasis. Isosorbide di‐(methyl fumarate) (IDMF), a novel derivative of DMF, was synthesized to circumvent this adverse reaction and unlock the potential of topical delivery, which could be useful for treating psoriasis in the subpopulation of psoriatic MS patients, as well as in the general population. Here, we compared its therapeutic potential of this non‐sensitizing derivative with DMF and its therapeutic version Diroximel in three skin‐ and neuroinflammation models: the lck‐GFP zebrafish, activated BV‐2 murine microglia and human T‐lymphocyte Jurkat cell line. The results provide a comparative evaluation of the bioactivity of these three related chemical entities in models relevant to skin and neuroinflammation and expose several therapeutic advantages unique to IDMF.